A unidade da igreja como manifestação da unidade de Deus: uma análise exegético-teológica de Efésios 4.1-6 - Jung, Marcelo (2011)
An exegetical-theological analysis of the theme of unity of the church from the text of Ephesians 4:1-6. First, are observed facial features of the text, from the textual analysis, literary and formal Greek text. Then we question by the feet of the text, which addresses the questions of the historicity of the text, the problem of its external sources and the possibility of analysis from the historical marks of the text itself. In the third step, the heart of the text is observed by analysis of content and theology. Finally we seek to see through the eyes of the text and see realities and contexts for your updates. The central finding is characteristic of the unity of the church as a eschatological reality of the manifestation of the unity og God in the world. This unit has triple anchoring: the call made ​​by God; the reality of unity and oneness of God Himself - Father, Son and Holy Spirit, and the eschatological goal of the unity of the cosmos in God.